Timing of parturition in dairy cattle - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1988)
A recent survey of calvings of dairy heifers and cows revealed that fall calvings occurred in a nonrandom pattern. The survey was conducted in a large 5,000-cow herd in which pregnant females were watched 24 hr/day. Fewer (P<.005) calves (42%) were born during the night-time hours of darkness (6 p.m. to 6 a.m.) than during daylight hours (58%). The time of day when calving occurred was unrelated to the duration of pregnancy or to any of the climatic variables measured, including daily temperatures (highs or lows), barometric pressure, relative humidity, precipitation, average wind velocity, or percentage of sunshine. Although some reports and popular opinion have suggested that time of calving might be influenced partly by prevailing weather conditions, our data fail to support this notion. We are unable to explain the observed nonrandom pattern of calving, except that it might be influenced by other management routines on the farm.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Parturition; Barometric pressure; Climate